2012
DOI: 10.1161/circimaging.112.974428
|View full text |Cite
|
Sign up to set email alerts
|

Normal Values of Left Atrial Volume in Pediatric Age Group Using a Validated Allometric Model

Abstract: 2, respectively, and was validated against an independent sample. The mean indexed LAV±SD for BSA≤1 m 2 and >1 m 2 is 31.5±5.5 mL and 26.0±4.2 mL, respectively, and was used to derive Z-scores. Conclusions-This

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 20 publications
(29 reference statements)
0
29
1
1
Order By: Relevance
“…Recently, Bhatla et al reported that (1) LAV/BSA 1 depends on BSA; (2) LAV/BSA 1 reduces as BSA reduces; and (3) LAV/BSA 1 was approximately 10 ml/m 2 in patients with BSA=0.2 m 2 , which is significantly smaller than that in adults. 16 Similarly, Jantzen et al reported 11.7±4.2 ml/m 2 in normal neonates with a mean BSA of 0.19 m 2 . 14 Khositseth et al used the prolate ellipse method, in which 3-dimensional diameters are multiplied, to calculate LAV, and assessed the relationship between LAV/BSA 1 and PDA in preterm infants with gestational age <33 weeks.…”
Section: Reference Value and Body Size Correction Of Lav In Elbwismentioning
confidence: 86%
See 4 more Smart Citations
“…Recently, Bhatla et al reported that (1) LAV/BSA 1 depends on BSA; (2) LAV/BSA 1 reduces as BSA reduces; and (3) LAV/BSA 1 was approximately 10 ml/m 2 in patients with BSA=0.2 m 2 , which is significantly smaller than that in adults. 16 Similarly, Jantzen et al reported 11.7±4.2 ml/m 2 in normal neonates with a mean BSA of 0.19 m 2 . 14 Khositseth et al used the prolate ellipse method, in which 3-dimensional diameters are multiplied, to calculate LAV, and assessed the relationship between LAV/BSA 1 and PDA in preterm infants with gestational age <33 weeks.…”
Section: Reference Value and Body Size Correction Of Lav In Elbwismentioning
confidence: 86%
“…In contrast, as shown in Figure 1D, LAV/BSA 1.54 (23.5±9.3 ml/m 3.08 ) did not depend on BSA (P=0.72). This model met all the following validation criteria: 16 (1) LAV/BSA 1.54 showed no significant residual relationship to BSA ( Figure 1D); (2) the intercept of LAV with BSA 1.54 for this group was not significantly different from zero (0.0028 ml, P=0.95); and (3) minimal heteroscedasticity was observed by visual inspection. Similarly, AE was 1.52 for LAV4CV.…”
Section: Patientsmentioning
confidence: 88%
See 3 more Smart Citations